The Attitudes About Parenting Strategies for Anxiety Scale: A Measure of Parenting Attitudes About Protective and Intrusive Behavior. (December 2019) - Kiel, Elizabeth J.; Wagers, Keshia B.; Luebbe, Aaron M.
Protective and intrusive parenting behaviors consistently relate to children's anxiety development. We present two studies describing the development of the Attitudes about Parenting Strategies for Anxiety (APSA) scale, which assesses parent distress about children's displays of anxiety and shyness as well as parent attitudes about the effectiveness of protective and intrusive responses across several domains. Study 1 included 594 parents who completed the APSA and additional measures online and established the factor structure, internal reliability, and validity of the measure. We also performed a latent profile analysis of the attitude items to understand common patterns and their correlates. Study 2 comprised 108 mothers participating in a laboratory-based study and provided additional evidence for the factor structure, reliability, and validity, as well as 1-year stability. The APSA appears to be a reliable and valid measure that could have utility for understanding the determinants of parenting behaviors relevant to child anxiety development.